2001
DOI: 10.1093/toxsci/63.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beta-Estradiol and Bisphenol A on Heat Shock Protein Levels and Localization in the Mouse Uterus Are Antagonized by the Antiestrogen ICI 182,780

Abstract: Bisphenol A (BPA) exhibits many estrogen-like effects in the rodent uterus, but not all of these can be attenuated by antiestrogens. This suggests the involvement of alternate pathways of BPA action that do not involve the estrogen receptor (ER). An examination of the in vivo effects of BPA on uterine gene expression and protein levels should contribute to an understanding of its mechanism of action. In this study we examined the dose-related effects of BPA on levels of a suite of heat shock proteins (hsps) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…MED induced a nonsignificant increase in hsp90α levels, decreased hsp72 levels, and had no effect on uterine weight. As in our previous study (Papaconstantinou et al 2001), the results of this study suggest a correlation between increases in hsp levels and uterine proliferation. This is not surprising, because several studies have shown that hsps can activate protein kinases and other cell-signaling proteins that stimulate cell proliferation and inhibit apoptosis (Kaur et al 2000;Mizuno et al 2001;Neckers et al 1999;Zhang et al 2001).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…MED induced a nonsignificant increase in hsp90α levels, decreased hsp72 levels, and had no effect on uterine weight. As in our previous study (Papaconstantinou et al 2001), the results of this study suggest a correlation between increases in hsp levels and uterine proliferation. This is not surprising, because several studies have shown that hsps can activate protein kinases and other cell-signaling proteins that stimulate cell proliferation and inhibit apoptosis (Kaur et al 2000;Mizuno et al 2001;Neckers et al 1999;Zhang et al 2001).…”
Section: Discussionsupporting
confidence: 90%
“…This argues for a role of the ER in the regulation of these genes in the uterus and is supported by our previous observations that E 2 and BPAinduced increases in hsp levels are antagonized by the ER antagonist ICI 182,780 (Papaconstantinou et al 2001). Whether ER agonists directly affect the transcriptional activity of theses hsp genes is uncertain.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations